Analysis of Sustainable Business Performance in Staple Food Traders in West Java Province: An Empirical Analysis (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
Climate change has resulted in an increase in global temperatures, causing an increase in the frequency of extreme weather events such as floods and hurricanes which then give rise to a chain of exposure to infectious diseases. Business and trade are also exposed to transitional risks arising from society's response to climate change. One way for traders to address the impacts of climate change is to create operating performance to improve sustainable business performance. Sustainable business performance also helps traders define their goals, measure their performance, and manage any changes to ensure their operational are more sustainable. In this study, SEM-PLS testing on staple food traders in West Java Province was used to find that sustainable business performance was influenced by operational performance using strategic supplier partnerships and quantity discounts.